Evaluation of the in vitro interaction of amoxicillin and cotrimoxazole antibiotics against resistant bacterial strains - Olufunmiso Olusola Olajuyigbe & , Olufunke Oyedeji and Otunola Adedayo (Journal of Applied Pharmaceutical Science, 2014)
The in vitro combination effects of amoxicillin and cotrimoxazole on clinical isolates was investigated using the agar diffusion and macrobroth dilution methods. The results showed that these organisms had varied susceptibility to the different concentrations of each of these antibiotics and their combinations. The susceptibility of the isolates to the antibacterial combinations showed that they were susceptible in the following order: Streptococcus pyogenes (TD2) > Streptococcus pyogenes (TD10) > Streptococcus pneumoniae (TE10) > Salmonella typhi (TC6) > Salmonella typhi (TC2). The macrobroth assay showed a drastic reduction in the minimum inhibitory concentrations of both antibiotics. While the MIC of amoxicillin ranged between 0.1202 and 0.4808 µg/ml and that of cotrimoxazole ranged between 0.2405 and 0.9619 µg/ml, the MIC of the antibacterial combinations ranged between 0.00305 and 0.0150 µg/ml. A statistical analysis of the zones of inhibitions produced by the antibiotics and their combinations indicated that the mean differences between the zones of inhibitions were significantly diverse. This study showed that there was synergistic interaction between amoxicillin and cotrimoxazole in vitro and could be an alternative choice of therapy for the treatment of streptococcal and gastrointestinal infections in which these organisms have been implicated.
Keywords: Antibacterial combinations, drug-drug interaction, synergy, antibiotics, bacteria.